Towards a coherent Data Life Cycle in Astroparticle Physics. (April 2020) - Tokareva, V; Haungs, A; Kang, D; Kostunin, D; Polgart, F; Wochele, D; Wochele, J
Abstract: The German-Russian Astroparticle Data Life Cycle Initiative (GRADLCI) aims to develop a data life cycle (DLC), namely a clearly defined and maximally automated data processing pipeline for a combined analysis of data from the experiment KASCADE-Grande (Karlsruhe, Germany) and experiments installed at the Tunka Valley in Russia (TAIGA). The important features of such an astroparticle DLC include scalability for handling large amounts of data, heterogeneous data integration, and exploiting parallel and distributed computing at every possible stage of the data processing. In this work we provide an overview of the technical challenges and solutions worked out so far by the GRADLCI group in the framework of a far-reaching analysis and data center. We will touch the peculiarities of data management in astroparticle physics and employing distributed computing for simulations and physics analyses in this field.